Increased amygdala activation to averted versus direct gaze in humans is independent of valence of facial expression - Straube, Thomas; Langohr, Bernd; Schmidt, Stephanie; Mentzel, Hans-Joachim; Miltner, Wolfgang H. R. (NeuroImage, 2010)
A recent study in monkeys showed that averted gaze displayed by conspecifics activates the amygdala regardless of the valence of facial expression (angry, neutral, appeasing). In contrast to this result, previous findings on amygdala activation to gaze information in humans have been mainly interpreted in terms of threat-related processing of facial signals. In the present event-related functional magnetic resonance imaging study with humans, we investigated brain responses to angry, happy, and neutral faces with either direct or averted gaze. Averted versus direct gaze induced increased amygdala responses regardless of facial expression. This finding suggests a critical role of the amygdala in gaze processing independently of the valence of facial expression. Furthermore, the effect of gaze on amygdalar responses seems to be preserved across nonhuman and human primates. © 2009 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Attention; Emotion; Eyes; fMRI; Gaze; Threat